Environmental implications of agriculture trade in Nepal - Pant, Krishna P. (Journal of Agriculture and Environment, 2007)
International trade of the goods and services has implications to environment via their effects on environment on production and consumption. Agriculture being closely linked with the natural environment the trade of agricultural products and the inputs required for agriculture affects the environment. This paper attempts to identify and analyze trade issues of environmental protection that mainly falls under the purview of Agreement on Technical Barriers to Trade under the World Trade Organization. The analyses will be helpful to identify and understand trade remedy measures that protect environment required for more sustainable agricultural development. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 30-37